2006
DOI: 10.1007/s10350-006-0612-4
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Tegafur Suppositories for Resectable Rectal Cancer: Phase II Trial

Abstract: Preoperative tegafur suppositories are associated with low toxicity and may lead to anal sphincter-sparing surgery with acceptable postoperative complications and favorable local and distal control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 38 publications
1
12
0
1
Order By: Relevance
“…the venous administration of 5-FU/leucovorin, consistent with the results of a similar study using tegafur suppositories [10,16]. In fact, tegafur suppositories can be used as an alternative adjuvant chemotherapy treatment, leading to a reduction in adverse effects.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…the venous administration of 5-FU/leucovorin, consistent with the results of a similar study using tegafur suppositories [10,16]. In fact, tegafur suppositories can be used as an alternative adjuvant chemotherapy treatment, leading to a reduction in adverse effects.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, our results support the importance of the preoperative administration of fluorouracil, which prevents postoperative recurrence regardless of the route of administration. A previous study reported that preoperative tegafur suppositories can lead to anal sphincter-sparing surgery with acceptable postoperative complications and a 4-year OS rate of 80.1% with favorable local and distal control among advanced rectal cancer patients [10]. Despite the use of this relatively old drug, our findings may provide new insights into standardized modern adjuvant cancer chemotherapy for advanced nonmetastatic colorectal cancer.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations